Associations of moderate-to-vigorous-intensity physical activity and body mass index with glycated haemoglobin within the general population: a cross-sectional analysis of the 2008 Health Survey for England. Issue 4 (3rd April 2017) - Bakrania, Kishan; Yates, Thomas; Edwardson, Charlotte L; Bodicoat, Danielle H; Esliger, Dale W; Gill, Jason M R; Kazi, Aadil; Velayudhan, Latha; Sinclair, Alan J; Sattar, Naveed; Biddle, Stuart J H; Hamer, Mark; et al.
Abstract : Objectives: To investigate the associations of objectively measured moderate-to-vigorous-intensity physical activity (MVPA) and body mass index (BMI) with glycated haemoglobin (HbA1c) in a national sample of English adults. Methods: The 2008 Health Survey for England data were used with 1109 participants aged ≥18 providing complete data. MVPA time was assessed using an accelerometer. Weighted linear regression models, adjusted for several confounders, quantified the associations between continuous measures of MVPA and BMI with HbA1c. Interaction analyses were implemented to observe whether the association of MVPA with HbA1c was modified by BMI or vice versa. Further weighted linear regression models examined the differences in HbA1c across four mutually exclusive categories of MVPA and BMI: (1) 'physically active and non-obese', (2) 'physically active and obese', (3) 'physically inactive and non-obese' and (4) 'physically inactive and obese'. 'Physically active' was defined as: ≥150 min/week of MVPA. 'Obese' was defined as: BMI ≥30.0 kg/m 2 . A wide range of sensitivity analyses were also implemented. Results: Every 30 min/day increment in MVPA was associated with a 0.7 mmol/mol (0.07% (p<0.001)) lower HbA1c level. Each 1 kg/m 2 increment in BMI was associated with a 0.2 mmol/mol (0.02% (p<0.001)) higher HbA1c level. The association of MVPA with HbA1c was stronger in obese individuals (−1.5 mmol/mol (−0.13% (p<0.001))) than non-obese individuals (−0.7 mmol/mol (−0.06% (p<0.001))); p=0.004 for interaction. The association of BMI with HbA1c remained stable across MVPA categories. Compared with individuals categorised as 'physically inactive and obese', only those categorised as 'physically active and obese' or 'physically active and non-obese' had lower HbA1c levels by 2.1 mmol/mol (0.19% (p=0.005)) and 3.5 mmol/mol (0.32% (p<0.001)), respectively. Sensitivity analyses indicated robustness and stability. Conclusions: This study emphasises the importance of physical activity as a determinant of HbA1c, and suggests that the associations may be stronger in obese adults.